Development of Digital Puzzle Based on Indonesian Traditional Houses as Virtual Manipulative Learning Media for Plane Geometry - Rachman, Kufita; Mas’ud, Azza Ilvana; Vesya, Siti Raihani; Arbiyanti, Ade Putri; Rasyid, Ilham (Unnes Journal of Mathematics Education, 2025)
The gap between the theory of plane geometry and real-life contexts occurs because the media often used only teach procedurally, resulting in weak conceptual understanding among students. Based on this, this research aims to develop a digital puzzle based on traditional houses that is suitable and practical for use as a virtual manipulative medium to bridge contextual understanding toward conceptual understanding. This research used a Research and Development (R&D) design and the 4-D model (define, design, develop, and disseminate) with interview guidelines and feasibility and practicality questionnaires as instruments, which were administered to 25 fourth-grade elementary school students. The results of validation by content and media experts indicate a very feasible category with feasibility percentages of 88% and 97.5%. This media is considered very practical to use, with a practicality percentage of 81.7%. These findings show that Digital Puzzle Media based on Traditional Houses is well-suited for teaching plane geometry in elementary school.